Specification of CPN models into MAS platform for the modelling of social policy issues: FUPOL project. (1st January 2014) - Piera, Miquel Angel; Buil, Roman; Mota, Miguel Mujica
Simulation transparency is becoming more crucial in the decision making process when quantitative computer tools are used to justify some strategies. The coloured petri net (CPN) formalism is a promising modelling approach to foster simulation transparency by means of state space traceability tools, which have been proven to be useful for modelling system dynamics with conflict patterns. E-governance is one of these areas in which the use of a multi agent system (MAS) to represent social dynamics in a certain urban context could be used to engage citizens in the design of urban policies that affects their habitat environment. In this paper a modelling methodology to represent and analyse a context-aware multi agent-based system, which tends to be highly complex is proposed. CPN models are used to specify citizen's preferences and affinities in front of an urban contextual change, while MAS is used to evaluate the social dynamics by translating the CPN semantic rules into agent's rules in NetLogo.